Characterization of Microbiomes Associated With the Early Life Stages of Sea Cucumber Apostichopus japonicus Selenka - Yu, Juanwen; Sakai, Yuichi; Mino, Sayaka; Sawabe, Tomoo (Frontiers in Marine Science, 2022)
There is a lot of evidence indicating pioneer microbes in early life having various effects on later host biology. Because of the influential phylogenetic position of sea cucumber, which is a deep branching clade in Deuterostomia, the attention on the microbiome in sea cucumber has been increasing. Although microbes in sea cucumber have been reported in several studies, there is a lack of knowledge regarding the pioneer microbiota in the early life stages of sea cucumber. In this study, microbiota changes during the larval development of sea cucumber were assessed using a laboratory rearing system. Microbial community structure was likely to be related to the developmental stage and significant alterations were detected in the late auricularia stage. The relative abundances of Oceanospirillales, Alteromonadales, and Rhodobacterales significantly varied after gut formation. A total of 257 strains were isolated from larval developmental stages of sea cucumber and affiliated to 124 ASVs in the metagenomic analysis. This data demonstrates for the first-time dynamic changes of sea cucumber microbiota in the developmental stages in early life.